A Flexible Capacitance Strain Sensor with Stitched Contact Terminals. Issue 2 (7th November 2022) - Kumar, Nimal Jagadeesh; Johnson, Alexander; Roggen, Daniel; Münzenrieder, Niko
Abstract: Flexible strain sensing in wearables and textiles, employs simple resistive sensor elements which suffer from high hysteresis. Textile compatible capacitive strain sensors that have low hysteresis and negligible cross‐axis sensitivity will be ideal for sensing human movement and shape change. In this work, a non‐MEMS based flexible interdigital capacitive strain sensor is proposed. The proffered sensor is built using flexible elastomer material with stitched conductive threads serving as internal and external contacts thereby making the sensor easily customizable. The developed sensor is amenable for fabrication using large scale textile sensor manufacturing techniques. The low sensitivity due to the low dielectric constant of most elastomers is addressed by employing high dielectric constant additives while molding the elastomer sections. The developed sensor is virtually insensitive to cross‐axis strain by design and is capable of withstanding stretching up to 160%. The prototype sensor built and tested has a sensitivity of 0.335 p F p F / m m m m ${\bf 0}{\bf .335}\frac{{{\bf pF}}}{{{\bf pF}}}{\bf /}\frac{{{\bf mm}}}{{{\bf mm}}}$ and portrays a worst‐case nonlinearity error of <±2.9%. An application, where the developed sensor was stitched on to a glove to sense finger movement is presented and discussed. The proposed fully stitch‐able sensors have the versatility to perform fabric‐based wearable strain sensing for body shape and movement analysis. Abstract : This paper presents a fully flexible capacitive strain/stretch sensor using a machine friendly non‐MEMS process for textile‐based sensing. The substrate uses a barium titanate infused silicone for its high dielectric characteristic. The sensor also uses a conductive thread‐based contacting for easier textile integration. The characteristics of the sensor along with validation by stitching the sensor onto a glove to monitor finger movement is presented.